Urban Politics and Space in the Nineteenth and Twentieth Centuries : Regional Perspectives. - Doyle, Barry M. (Cambridge Scholars Pub., 2007)
This book addresses the increasing regionalisation of urban governance and politics in an era of industrialisation, suburbanisation and welfare extension. It provides an important reassessment of the role, structure and activities of urban elites, highlighting their vitality and their interdependence and demonstrating the increasing regionalisation of municipal politics as towns sought to promote themselves, extend services and even expand physically onto a regional level. Moreover, it expl ...